Laguna Sheepherding. Issue 3 (2nd July 2016) - Hopkins, Maren P.; Colwell, Chip; Ferguson, T. J.
Abstract : In the U.S. Southwest, the introduction of domesticated animals in 1540 dramatically changed Native American subsistence strategies and cultural practices. Pueblo communities across the Southwest quickly adopted sheep into their diet and became dedicated sheepherders within a century, coming to hold herds numbering into the thousands. The Pueblo of Laguna, in west-central New Mexico, became especially focused on sheepherding in the mid-1800s, and by the early 1900s were more pastorally oriented than any other Pueblo. This article examines Laguna sheepherding practices around Mount Taylor, focusing especially in the San Mateo Basin. Synthesizing archaeological, ethnographic, and documentary sources, we investigate the apex of Laguna sheepherding, from 1862 to 1940, to provide a detailed description of Laguna sheepherding practices. With the foundation of a broad understanding of Laguna sheepherding, we also explore whether the material remnants of sheepherding can be archaeologically linked with particular tribes. We conclude that associating specific sheepherding sites with the Laguna solely on the basis of archaeological data is extremely difficult. As a result, archaeologists should be cautious in culturally labeling sites, and must use collaborative ethnographic and historical methods to more fully illuminate the remnants of sheepherding heritage that persist in New Mexico and beyond.